Aflatoxin B1 disrupts the androgen biosynthetic pathway in rat Leydig cells (2014)
The present study investigated if Aflatoxin B1 (AFB1), a potent and naturally occurring mycotoxin, interferes with the steroidogenic pathway in rat Leydig cells. Testicular Leydig cells are the predominant source of the male sex steroid hormone testosterone (T) that maintains the male phenotype and support fertility. Leydig cells, isolated from 35-day-old male Long-Evans rats (Rattus norvegicus), were incubated with AFB1 at 0, 0.01, 0.1, 1, 10 lM followed by measurement of T secretion by radioimmunoassay and analysis of protein expression in western blots. Results demonstrated that AFB1 suppressed testosterone secretion in a dose-dependent manner and inhibited expression of cholesterol transporter steroidogenic acute regulatory protein (StAR) and steroidogenic enzymes [(3b-hydroxysteroid dehydrogenase (3b-HSD) and 17b-hydroxysteroid dehydrogenase enzyme (HSD17B3)]. Protein expression analysis showed that AFB1 treatment increased ERK phosphorylation but suppressed p38 MAPK and JNK activation in Leydig cells. AFB1-induced inhibition of Leydig cells was alleviated by co-treatment with the ERK inhibitor UO 126, implying that ERK mediates, at least in part, the inhibitory effects of AFB1 in Leydig cells. The findings highlight potential extra-hepatic effects of aflatoxin exposure and indicate that exposure to AFB1 has significant reproductive health implications for consumers of contaminated products even under conditions of low dietary toxin levels.